1989
DOI: 10.1073/pnas.86.18.6913
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Xenopus oocytes of rat liver mRNA coding for a bile salt-dependent cholesteryl ester hydrolase.

Abstract: BiochemistryExpression in Xenopus oocytes of rat liver mRNA coding for a bile salt-dependent cholesteryl ester hydrolase (pancreatic cholesteryl esterase/neutral cholesteryl esterase/sodium cholate)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…The identity of a second cytosolic cholesterol esterase as being CEL was first established by Camulli et al (6), who purified the protein from rat liver and showed that it was identical to the pancreatic enzyme based on immunoreactivity with CEL-specific antibodies, bile salt activation, and N-terminal amino acid sequencing. These results were subsequently confirmed by RNA analysis (4,7,65). The hepatic CEL was found to be present in specific endosomal compartments of hepatocytes (127).…”
Section: Hepatic Lipoprotein Metabolismsupporting
confidence: 67%
See 1 more Smart Citation
“…The identity of a second cytosolic cholesterol esterase as being CEL was first established by Camulli et al (6), who purified the protein from rat liver and showed that it was identical to the pancreatic enzyme based on immunoreactivity with CEL-specific antibodies, bile salt activation, and N-terminal amino acid sequencing. These results were subsequently confirmed by RNA analysis (4,7,65). The hepatic CEL was found to be present in specific endosomal compartments of hepatocytes (127).…”
Section: Hepatic Lipoprotein Metabolismsupporting
confidence: 67%
“…In addition to its presence in the digestive tract, CEL is synthesized in liver (4,7,65), macrophages (9,46), endothelial cells (10), and heart (116). CEL protein and enzyme activity are also found in the circulation (117)(118)(119).…”
Section: Lipoprotein Metabolism and Atherosclerosismentioning
confidence: 99%
“…8 -11 In subsequent studies, however, we showed that RNA extracted from a pool of rat livers contained CEH mRNA, indicating at least in some cases, a capacity for hepatic synthesis of the enzyme. 12 These findings were confirmed and extended by Hui, Brockman, and their colleagues (Kissel et al 2 and Camulli et al 13 ), who reported that the rat liver can contain both mRNA and protein species indistinguishable from pCEH message and protein. However, Schotz and his colleagues (Reue et al u ) have recently reported that rat liver does not contain CEH mRNA.…”
supporting
confidence: 76%
“…12 Briefly, for each RNA sample, 25-50 oocytes collected from Xenopus laevis were injected with 50 nl of a solution of either mRNA (2 mg/ml in water) or total RNA (3 mg/ml). Oocytes were incubated at 19°C for 3-5 days.…”
Section: Preparation and Microinjection Of Xenopus Laevis Oocytesmentioning
confidence: 99%
“…Total RNA was isolated from hepatic cells at the conclusion of the experiments using a guanidinium thiocyanate-based procedure ( 19) as previously described (20). RNA samples were blotted onto nylon membranes (Nytran, Schleicher & Schuell, Inc., Keene, NH), using a Bio-Rad Laboratories (Richmond, CA) manifold following the manufacturer's protocol.…”
Section: Rna Isolation and Quantitationmentioning
confidence: 99%